2012
DOI: 10.1177/1063426611428157
|View full text |Cite
|
Sign up to set email alerts
|

Engagement in Trauma-Specific CBT for Youth Post-9/11

Abstract: Treatment participation was examined among youth enrolled in an evaluation of cognitive behavioral therapy (CBT) for trauma following the 9/11 World Trade Center disaster. Staff at nine agencies serving a predominantly low-income ethnically diverse population were trained to deliver CBT and structured engagement strategies. Four hundred and forty-five youth ages 5-19 were eligible for CBT, and 417 (94%) received at least one treatment session. Pretreatment and treatment show rates and overall dose were examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 39 publications
(70 reference statements)
1
4
0
Order By: Relevance
“…Predisposing and need factors identified in the EBMVP model were not associated with treatment initiation or treatment completion in our sample. Our results are partially consistent with a past study that found demographic variables added only a small amount variance that explained pretreatment show rates and dose in a sample of trauma-exposed youth offered TIC interventions (Rodriguez et al, 2013). Our results contradict the literature that suggests greater symptom severity or greater need is an important predictor of mental health service use (Miller et al, 2008).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Predisposing and need factors identified in the EBMVP model were not associated with treatment initiation or treatment completion in our sample. Our results are partially consistent with a past study that found demographic variables added only a small amount variance that explained pretreatment show rates and dose in a sample of trauma-exposed youth offered TIC interventions (Rodriguez et al, 2013). Our results contradict the literature that suggests greater symptom severity or greater need is an important predictor of mental health service use (Miller et al, 2008).…”
Section: Discussionsupporting
confidence: 92%
“…Only 43.0% of the total sample of youth actually completed treatment, consistent with research suggesting between 20 and 75% of youth prematurely drop out of therapy (Olfson et al, 2009; Wamser-Nanney & Steinzor, 2017). Previous studies found treatment initiation rates among low-income, urban populations ranging from 72% (McKay, Lynn, & Bannon, 2005) to 95% (Rodriguez et al, 2013) and treatment completion rates of 59% (McKay et al, 2005). Several plausible explanations for high rates of initiation and completion among those who initiated our TIC interventions exist.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations